2016
DOI: 10.1089/end.2015.0724
|View full text |Cite
|
Sign up to set email alerts
|

A Minimally Invasive Method in Diagnosing Testicular Torsion: The Initial Experience of Scrotoscope

Abstract: Purpose: To introduce scrotoscopy in the diagnosis of testicular torsion and evaluate its value in clinical application.Patients and Methods: From February 2010 to June 2013, 14 patients, aged 12 to 24 years, were included into this study due to acute onset of scrotal pain. On Doppler ultrasound imaging, the blood flow decreased in seven cases (including two “no flow” cases) and remained normal in the other seven. Following anesthesia, a 10F pediatric cystoscope employed as scrotoscope was inserted into the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Conversely, scrotoscopy seems to have a diagnostic value beyond ultrasound. The diagnosis of TT by scrotoscopy has earlier been reported in China [ 20 ] ; their conclusion agrees with those of this study, both reporting 100% sensitivity and specificity of scrotoscopy for diagnosing TT. The difference between these 2 reports was that in the case of this study, we tried to grade the status of TT for the first time using a scrotoscope, and then performed a chi-square test to find the differences and consistency between scrotoscope grading and ultrasound/BSG during OS after testicular detorsion.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, scrotoscopy seems to have a diagnostic value beyond ultrasound. The diagnosis of TT by scrotoscopy has earlier been reported in China [ 20 ] ; their conclusion agrees with those of this study, both reporting 100% sensitivity and specificity of scrotoscopy for diagnosing TT. The difference between these 2 reports was that in the case of this study, we tried to grade the status of TT for the first time using a scrotoscope, and then performed a chi-square test to find the differences and consistency between scrotoscope grading and ultrasound/BSG during OS after testicular detorsion.…”
Section: Discussionsupporting
confidence: 92%
“…Scrotoscopy is a minimally invasive procedure, and has been increasingly used in scrotal diseases. [5,7,8,17] In the present study, scrotoscopic examination successfully identified TR in all 9 patients, without a false positive case (0/6). The operation did not take much time, taking only 5–13 min.…”
Section: Discussionsupporting
confidence: 60%
“…Their study proved that MECS may be a safe, effective, and encouraging technique for EC treatment. In 2016, Ye et al [ 7 ] employed a pediatric cystoscope as a scrotoscope to examine the testis/epididymis of patients with acute onset of scrotal pain and verified that it was a minimally invasive, safe, and effective approach for the early diagnosis of testicular torsion (100% specificity and sensitivity).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Yan et al [ 6 ] were the first to treat testicular hydrocele with the aid of a scrotoscope, providing a viable and encouraging technique for the diagnosis and treatment of hydrocele. Furthermore, in 2016, Ye et al [ 7 ] verified that scrotoscopy was a minimally invasive, safe, and effective approach for the early diagnosis of testicular torsion.…”
Section: Introductionmentioning
confidence: 99%